(u+4)(u-2)=-5

Simple and best practice solution for (u+4)(u-2)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (u+4)(u-2)=-5 equation:



(u+4)(u-2)=-5
We move all terms to the left:
(u+4)(u-2)-(-5)=0
We add all the numbers together, and all the variables
(u+4)(u-2)+5=0
We multiply parentheses ..
(+u^2-2u+4u-8)+5=0
We get rid of parentheses
u^2-2u+4u-8+5=0
We add all the numbers together, and all the variables
u^2+2u-3=0
a = 1; b = 2; c = -3;
Δ = b2-4ac
Δ = 22-4·1·(-3)
Δ = 16
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{16}=4$
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-4}{2*1}=\frac{-6}{2} =-3 $
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+4}{2*1}=\frac{2}{2} =1 $

See similar equations:

| -4(-7x+1)-8x=2(x-5)-8 | | 154=-4(8-6r)+24r | | 17.2x+3=12+17.1x | | −2u+2=−7u+17 | | -3=n-6 | | 6(c-6)=48 | | 4x+x+2=11x-6x=2 | | 4x+1=1.3333x+10 | | 32=n+16 | | 4x+1=1.33x+10 | | -29=-19+x | | -3+1/9x-6=1 | | 298.6=135.4+q1297.6 | | 4(4x+3)=21x+7-5x+5 | | -10(x-2)=3x-59 | | 254=39-y | | 1+4c=27 | | 13-4(x)=-11 | | 57=-19p | | 1+3x=x-2-4x | | 7x+17x-6=6(4+8) | | 6(x+2)=5x+97 | | x(2x+6)=126 | | 1/2(x+1)(3x-7)=8 | | -4n+1=73 | | 14x11/22=x | | 25+10d(117-d)=1575 | | 7x+13-4=4(5x+8) | | 51x+40=48x+121 | | 5n+6+(−7n)=0 | | 3(5-2h)+9=-6 | | Y=5/4(x+7) |

Equations solver categories